Fatty acid components of rat-tissue lipids - Connellan, J. M. (1965)
1. The lipids of rat heart, kidney, skeletal muscle and liver were separated by chromatography on silicic acid into cholesterol ester, triglyceride, free-fatty acid and phospholipid fractions. 2. The fatty acid compositions of these fractions were determined by gas–liquid chromatography. 3. Palmitic acid was always present in highest concentration in the cholesterol ester fraction; oleic acid was present in greatest percentage in the triglyceride fraction; arachidonic acid was in highest concentration in phospholipid, and in lowest concentration in triglyceride fractions. 4. The fatty acid compositions of the cholesterol ester fractions were broadly similar for all the extrahepatic tissues. 5. Some differences in fatty acid composition of the phospholipids were evident between the hepatic and extrahepatic fractions.